Recent Advances in Smart Self-Healing Polymers and Composites - Li, Guoqiang; Meng, Harper (Woodhead Publishing, an imprint of Elsevier Ltd., 2015)
Recent Advances in Smart Self-Healing Polymers and Composites examines the advances made in smart materials over the last few decades and their significant applications in aerospace, automotive, civil, mechanical, medical, and communication engineering fields. Based on a thorough review of the literature, the book identifies "smart self-healing polymers and composites as one of the most popular, challenging, and promising areas of research. Readers will find valuable information compiled by a large pool of researchers who not only studied the latest datasets, but also reached out to leading contributors for insights and forward-thinking analogies.
Keywords: Self-healing materials.; elektronické knihy; electronic books